Writerly identities in Beur fiction and beyond - Reeck, Laura, 1972- (After the empire., 2011)
Writerly Identities in Beur Fiction and Beyond explores the Beur/banlieue literary and cultural field from its beginnings in the 1980s to the present. It examines the struggles of author-characters to attain self-identity and a place in the world through writing and authorship and engages this literary theme with a range of socio-cultural challenges facing contemporary France.